The value of urban and peri-urban conservation efforts within a global biodiversity hotspot - Ground, Lyle E.; Slotow, Rob; Ray-Mukherjee, Jayanti (African Biodiversity & Conservation, 2016)
Background: Systematic conservation planning (SCP) is a key tool in conservation prioritisation. It has recently been applied within the eThekwini Municipal Area (EMA), South Africa, a rapidly developing metro located within a biodiversity hotspot. Most vegetation types within this region are threatened, yet have received limited scientific attention. Objectives: To assess forb biodiversity of coastal and near-coastal grasslands and contextualise potential drivers of species variation to the EMA context. Method: We quantified forb species richness, frequency and species composition, determinedthe variation of these amongst plots and sites, and assessed which variables were responsible for this variation. Results: Site forb species richness ranged from 33 to 84 species per site, with the most frequent species differing across the seven sites. Beta diversity was higher across than within sites. Distance to the closest traditional medicine market and site perimeter-to-area ratio were the greatest drivers of species richness, whilst altitude, aspect, mean temperature and rainfall seasonality were the main contributors to species composition patterns. Conclusion: SCP can use key environmental and climatic categories to improve selection of grasslands to maximise both species richness and variation in species composition. A more fine-scale systematic conservation plan will, in turn, provide a more robust basis for development decisions. The outcomes illustrate the importance of urban and peri-urban conservation efforts, including fine-scale conservation planning, in contributing to regional, national conservation targets.